2020
DOI: 10.1039/c9tb02652e
|View full text |Cite
|
Sign up to set email alerts
|

CT/NIRF dual-modal imaging tracking and therapeutic efficacy of transplanted mesenchymal stem cells labeled with Au nanoparticles in silica-induced pulmonary fibrosis

Abstract: AA@ICG@PLL NPs, as CT/NIRF dual modal nanotracers, were synthesized to track BMSCs in the treatment of pulmonary fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 59 publications
1
19
1
Order By: Relevance
“…Bioluminescence imaging (BLI) which utilizes luciferase reactions also has the advantage of providing viability information of transplanted cells, but this method suffers from poor tissue penetration and low spatial resolution. MSCs can also be labeled with gold nanoparticle and tracked by computed tomography (CT) image in vivo [244,245]. These gold nanoparticles have advantage of exerting negligible influence on viability, proliferation, and differentiation ability of labeled MSCs, and offer good spatial resolution and long-term tracking when used in conjunction with CT modality [244].…”
Section: Methods Of Tracking Mscs In Vivomentioning
confidence: 99%
“…Bioluminescence imaging (BLI) which utilizes luciferase reactions also has the advantage of providing viability information of transplanted cells, but this method suffers from poor tissue penetration and low spatial resolution. MSCs can also be labeled with gold nanoparticle and tracked by computed tomography (CT) image in vivo [244,245]. These gold nanoparticles have advantage of exerting negligible influence on viability, proliferation, and differentiation ability of labeled MSCs, and offer good spatial resolution and long-term tracking when used in conjunction with CT modality [244].…”
Section: Methods Of Tracking Mscs In Vivomentioning
confidence: 99%
“…Mesenchymal stem cells (MSCs) have shown promising therapeutic effects on IPF [6]. In general, MSCs have therapeutic capability for repairing injured tissues by releasing extracellular vesicles (EVs) carrying various active cargoes [7].…”
Section: Introductionmentioning
confidence: 99%
“…Different types of NIR fluorescent NPs (such as quantum dots, rare-earth NPs, and organic fluorescent NPs) have been used for in vivo tracking of transplanted stem cells (Chen et al, 2018). It was confirmed that BMSCs labeled with AA@ICG@PLL NPs could be effectively transplanted into SiO 2 −induced PF mice, and then monitored by CT/NIR fluorescence dual-modality imaging for up to 21 days (Huang et al, 2020). Additionally, BMSCs were observed to migrate to damaged lung tissue when DiR-labeled BMSCs were transplanted into a SiO 2 −induced PF rat model (Li et al, 2018).…”
Section: Imaging-guided Therapymentioning
confidence: 94%